National, International and Legal Mechanisms of Control over the Activity of Non-Government Security Entities - M. V. Zavalnyi (Law and Safety)
The author of the article has studied the reasons for introducing a control mechanism over the activities of private security companies, which play an increasingly important role in the security sector worldwide. These companies by providing security services, directly influence the security, human rights and democratic order of the country. In this regard, it has been emphasized that the issues of legal regulation of the activities and responsibilities of private security companies are particularly important for society and the state.